Manifestation And Endoparacitic Intensity On Gonggong Conch (Laevistrombus turturella) - Muzahar Muzahar (EDP Sciences, 2021)
Habitat the gonggong conch (Laevistrombus turturella) also known as Dog conch is a species from the Gastropod class that can be found in shallow waters with muddy sand substrate. In Kepulauan Riau Province, these animals are hunted by fishermen to sell to consumers since gonggong conch is a favourite culinary in this province. The availability of conch in the market has only relied on natural catches. The high consumption and natural fluctuations have decreased the conch population. To maintain the sustainability of the dog conch, it is necessary to carry out the cultivation activities. The cultivation begins with the selection of quality broodstock. The gonggong conch of natural origin needs to be determined before cultivation, in order to prevent the entry of disease in the cultivation system i.e. parasites. This study includes the determination, prevalence and infection intensity of endoparasites in conch from Madong Bay, Tanjungpinang. The results showed that the total length of the conch shells ranged from 55.5 to 79.5 mm with an average length of 67.72 mm and a frequency mode of 64.6 mm. The sex ratio between male and female conch is 1:1.1 (not ideal) n=30. Two kinds of parasites were found in the digestive tract of gonggong conchs are conoidacid oocysts and trematode sporocysts. The number of endoparasites, prevalence and intensity in wild caught has high numbers involving conoidacid oocysts (prev=100%; I=48.23 ind/conch) and trematode sporocysts (prev=100%; I= 135.33 ind/conch). It was concluded that the level of endoparasites infection in the dog conch from the Madong Bay was categorized as moderate-to-severe.